Ketidakmampuan Anak Usia Dini Membedakan Realita Dan Rekayasa Dalam Berinterkasi Dengan Kecerdasan Buatan (AI) - Endang Lestari (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
The ability to distinguish between reality and engineering is one of the important aspects of children's cognitive development. The age range of 0-6 years of children's thinking skills is still concrete, imaginative, and does not have mature logic skills, so the boundaries between the real world and engineering are often converged, especially in interactions with artificial intelligence (AI) technologists who display responses as if they were real. The purpose of this study is to describe the form of early childhood inability to distinguish between reality and engineering, identify causative factors based on the stages of cognitive development, and explain its implications for children's parenting and education. This study uses a descriptive qualitative approach. Data collection by studying the literature on child development theory and direct observation of children's behavior, then analyzed by grouping data and drawing conclusions. The research location at RA Muslimat NU Cekok 3 Ponorogo, with 24 research subjects of group B students. The results of the study show that this inability is a natural phenomenon due to egocentric nature and a highly developed imagination. Children consider what is in their minds, fairy tales, or media as real reality. This condition is not a sign of abnormality or lies, but rather the stage of growth will slowly disappear with the maturity of thinking. Parents and educators are advised to use the world of imagination as a means of learning, while introducing real and artificial boundaries to children.